Nietzsche for nurses: caring for the Übermensch - Drummond, John S. (Nursing philosophy, 2000)
We hear much these days of lifelong learning and higher levels of nursing practice. We have even been introduced to the concept of the supernurse. This paper seeks to contribute an ethico-political dimension to the largely performative uses of these terms in contemporary nursing politics. This is done by exploring the promise of certain elements of Nietzsche's philosophy for nursing. Certain major Nietzschean themes are outlined in the context of modernity followed by their exploration in a nursing context. These themes come principally from Thus Spake Zarathustra, and include not only that of Übermensch (Superman), but also the related ideas of eternal recurrence, nihilism, and the last Man. It is argued that the conditions in which nurses now learn and practice have become increasingly instrumentalized and technorational to the extent that they are in danger of effecting a nihilism in what becomes a culture of perpetual obligation to those who would seek to measure our performance. It is against this background that Nietzsche's idea of the Übermensch is explored as a figure for self-overcoming the professional subjectivity that may be constructed in the face of these conditions. However, it will be seen that this raises certain issues which beg the question of the productive value of Nietzsche's philosophy in this particular context. At this point, in the last part of the paper, by considering the tensive relation between the discourse practices of present-day managerialism and nursing ethics, it is argued that it is these very problems that present the Übermensch as a tensive but potentially productive figure for nursing and nurse education in its broadest sense.